Customer Resource Management and Salesperson Behavior Optimization: The Application of Dynamic Pricing Systems - Li, Huiying (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper explores the importance of Customer Resource Management (CRM) in modern business environments, analyzes common issues faced by traditional salespeople in CRM, and examines how dynamic pricing systems can optimize the utilization of customer resources. Through a detailed case study and comprehensive analysis, the paper demonstrates the effectiveness of dynamic pricing systems in actual applications, providing new approaches and methods for companies to manage customer resources and enhance salesperson behavior.